Media article writing training to disseminate student activity programs to the community - Ferdinal, Ferdinal; Oktavianus, Oktavianus; Nopriyasman, Nopriyasman; Ferdi, Elzahra Rahmadini; Ferdi, Sultan Hakim (Community Empowerment, 2025)
One of the expected outcomes of the Student Community Service Program (Kuliah Kerja Nyata or KKN) is the publication of written works in online media. This community service activity aimed to facilitate students in producing online media articles based on the KKN programs they had implemented. The training material covered techniques for collecting and processing data from field activities into a media article. The training was attended by 19 students from Universitas Andalas. Data from observations, documents, and interviews were used as the basis for the written work. The training was conducted virtually through guidance, debriefing, mentoring, and monitoring via a WhatsApp group. A total of three training sessions were held on the Zoom Meeting platform, with a total duration of five hours, focusing on a range of writing competencies. Following the training, 17 participants (90%) successfully published their articles in seven online media in West Sumatra.